Development of STEM-Based E-Modules on Freshwater Fisheries to Facilitate 21st Century Skills - Ina Setiawati; Rahma Widiantie; Anna Fitri Hindriana; Edi Junaedi (Postgraduate, University of Mataram, 2024)
The urgency of this research lies in the pressing need for universities to align with Learning Process Standards, which mandate the development of teaching materials grounded in research findings. Such materials are crucial for nurturing highly skilled and competent graduates in various fields. Specifically, the creation of STEM-based E-Modules in freshwater fisheries courses is vital for equipping biology students with 21st-century skills. These skills are essential for applying scientific knowledge to real-life scenarios and for generating societal benefits through innovative products. The research method used is Research and Development design, using the PPE model, namely Planning, Production, and Evaluation. Data collection using expert team validation sheets and questionnaire sheets. Data analysis uses Miles and Hubermann analysis to analyze expert validation data. The results of validation by validators in the STEM-based freshwater fisheries E-Module include assessment results from media experts showing assessment results of 83% (very feasible) and assessment results from STEM content experts of 81% (very feasible). The results of the questionnaire by lecturers showed an average score of 83% (practical) and the results of questionnaires by students show an average score of 80% (practical). Based on the results of the study, it can be concluded that the developed STEM-Based E-Modules on Freshwater Fisheries can facilitate students to practice 21st century skills.